A Study on the Relationship Between Vitamin B12 Levels and Lipid Profile in Serum of Type 2 Diabetic Patients with Dyslipidemia in Thi Qar Province, Iraq - Abed, Zainab Ahmed (University of Thi-Qar Journal of Science, 2025)
This study aimed to investigate the relationship between serum vitamin B12 concentrations and lipid profiles in type 2 diabetic patients with dyslipidemia. We conducted this study in Thi Qar Province, Iraq, during the late summer and early fall of 2023. The investigation included 50 patients with confirmed type 2 diabetes and a comparison group of 50 healthy volunteers who helped establish baseline values. The findings were quite revealing that patients dealing with dyslipidemia showed much higher triglyceride, total cholesterol, LDL, and VLDL levels than our control group (P≤0.05). Conversely, HDL cholesterol levels were significantly reduced in this group (P≤0.05). we also noticed that Type 2 diabetics with dyslipidemia had considerably worse lipid profiles compared to those with normal lipid measurements. We found a relationship between vitamin B12 levels and abnormal lipid patterns in the dyslipidemia group. These findings suggest that monitoring vitamin B12 status should be considered as part of comprehensive lipid management strategies in type 2 diabetic patients. Our findings open doors to potential new treatment approaches, as B12 deficiency might be playing a significant role in lipid disorders among Type 2 diabetics - something that's often overlooked in current treatment protocols.